2016
DOI: 10.1016/s0140-6736(16)32429-1
|View full text |Cite
|
Sign up to set email alerts
|

Health, welfare, and the state—the dangers of forgetting history

Abstract: The art of medicine Health, welfare, and the state-the dangers of forgetting history Recent public policy in the UK has been dominated by a discourse which asserts that public expenditure on universal health coverage and welfare is a burden on the productive economy and unaffordable in what has been deemed a time of austerity. There is a widely held assumption that universal welfare provision, as offered by most modern, welfare states is a luxury, only afforded since the World War 2 by wealthier economies. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This perspective helps to illuminate the tools available to policy-makers and the interventions which could have a lasting impact. 2930…”
Section: Moving Towards More Dynamic Thinking: Power History and Thementioning
confidence: 99%
“…This perspective helps to illuminate the tools available to policy-makers and the interventions which could have a lasting impact. 2930…”
Section: Moving Towards More Dynamic Thinking: Power History and Thementioning
confidence: 99%
“…this theme was explored and illustrated by a fascinating study of the lessons from history by Szreter et al in The Lancet last year. 3 the authors concluded that 'the interests of the poor and the wealthy are not mutually opposed in a zero-sum game. Investment in policies that develop human and social capital will underpin economic opportunities and security for the whole population'.…”
Section: Good Health Is An Essential For a Prosperous Societymentioning
confidence: 99%
“…14 The productivity of those in work is higher, partly because health is better and people are not forced into low paid employment. 15 There is a clear and present danger that leading French politicians will seek to portray their country as a failing state in the race for votes this year. But if that can be avoided then we should not assume that the inequality and poor health that helped get Brexit over the line and Trump into power will necessarily play out that way in France.…”
Section: Figmentioning
confidence: 99%